(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
Learning reading skills through authentic materials is the best way for learners because authentic materials provide real- life examples of language used in everyday situations. This will stimulate pleasure reading since students feel they are not reading simply for a final grade. Thus, they would in their native language. Authentic materials refer to resources that are created for real-world communication and are not specifically designed for language learning purposes. These materials can include newspapers, magazines, advertisements, videos, podcasts, social media posts.